Teoria do conforto para promoção da saúde no cuidado de enfermagem à parturiente - Silveira, Isolda Pereira da (2010)
Comfort is expected for every woman going into labor in the form of aid, attention, presence and care of the obstetric nurse and the presence of family, the attendant, the doula and the entire team that is driving her to all kinds of care. It aims to uncover the comforting care for women during childbirth as a goal of nursing to health promotion in the contexts, physical, environmental, social and psycho. A descriptive study, qualitative approach, on the comfort women giving birth that is in labor. The place for the development of the study was the delivery center of a large public maternity hospital, in Fortaleza, Ceará. The subjects were nine pregnant women admitted to the Birth Center, in labor, without providing obstetric risk, and who agreed to voluntarily participate in the study. Data were collected from September to December 2009. Techniques were used as free observation and structured interviews. For the maintenance of records, it was used the field diary. Data analysis employed the method proposed by Bogdan and Biklen. With treatment and operation of the data analysis yielded the following categories: Significance of environmental comfort, Meaning of discomfort, Meaning of feeling comfortable, Meaning of comfort received. We believe in the awareness of the nursing workers as the discovery that the research has brought. It is appropriate that nurses reflect on the comfort with larger view. Depending on the outcome and has matured with the idea is to draw up a roadmap identifying the needs for comfort not satisfied by pregnant women, therefore, we direct the provision of midwifery care, focusing on the comfort women giving birth in health promotion Birth Center. The thesis argues attended and responded to that was made: the comfort and benefits to make up the practice of Obstetric Nursing focused on the parturient, a new vision - the addition of Obstetric Nursing care to promote health of the mother, based on the comfort women giving birth in physical contexts, environmental, psycho and social.